A GROUNDBREAKING WIN OR A CASTLE IN THE AIR? THE RELEVANCE OF THE GREEN POWER V. SPAIN AWARD IN THE EU-ISDS FEUD - Đajić, Sanja (Zbornik radova Pravnog fakulteta u Novom Sadu, 2023)
The EU and ISDS have been embroiled in an exhausting feud over intra-EU investment disputes which may still not reach its climax despite several dramatic and radical moves by the European Union and its Member States against the nearly unfettered resistance of the ISDS. Green Power v. Spain is the first international investment case in which the tribunal denied jurisdiction due to an incompatibility of the arbitration clause in the Energy Charter Treaty with EU law in light of the Achmea case, but also the first case where the rule of lex superior was employed to tip the scale in favour of EU law. The overview of the award will be presented against different backgrounds: massive investment case law uniformly denying intra-EU preliminary objections on one hand, and concerted actions of the EU and its Member States to construct a dam against intra-EU investment cases, on the other. The aim of this case note is to review the possible relevance of the Green Power v. Spain arbitral award and the argument that EU law is lex superior as a matter of international law, in pending and future intra-EU investment disputes, and to assess to what extent different factors, such as the seat and rules of arbitration and general rules of international law, molded the reasoning of the tribunal. The arbitral award is a meticulous decision with instructive arguments on how to situate supremacy of EU law within the law of treaties while navigating the rough waters of enduring conflicts amid different international agreements and between various levels of governance. Given that the tribunal offered a variety of reasons to uphold the applicability of EU law to determine jurisdiction, there is the distinct possibility that the award might have an impact on other investment tribunals.
Keywords: intra-EU investment disputes, Achmea, Green Power v. Spain, conflict of international obligations